2014
DOI: 10.1186/1471-244x-14-121
|View full text |Cite
|
Sign up to set email alerts
|

To what extent does the anxiety scale of the Four-Dimensional Symptom Questionnaire (4DSQ) detect specific types of anxiety disorder in primary care? A psychometric study

Abstract: BackgroundAnxiety scales may help primary care physicians to detect specific anxiety disorders among the many emotionally distressed patients presenting in primary care. The anxiety scale of the Four-Dimensional Symptom Questionnaire (4DSQ) consists of an admixture of symptoms of specific anxiety disorders. The research questions were: (1) Is the anxiety scale unidimensional or multidimensional? (2) To what extent does the anxiety scale detect specific DSM-IV anxiety disorders? (3) Which cut-off points are sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 44 publications
(52 reference statements)
1
27
0
1
Order By: Relevance
“…An improved understanding of GPs' diagnostic accuracy of anxiety disorders is a fundamental step in building better access to care and treatment for patients with anxiety disorders in PHC. Anxiety scales may help GPs to detect specific anxiety disorders [34,35] , but evidence of the added value of their use over routine clinical judgment is limited. We, therefore, performed a systematic review of data on accuracy of assisted and unassisted diagnoses of anxiety disorders by GPs, worldwide, in adults and children/adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…An improved understanding of GPs' diagnostic accuracy of anxiety disorders is a fundamental step in building better access to care and treatment for patients with anxiety disorders in PHC. Anxiety scales may help GPs to detect specific anxiety disorders [34,35] , but evidence of the added value of their use over routine clinical judgment is limited. We, therefore, performed a systematic review of data on accuracy of assisted and unassisted diagnoses of anxiety disorders by GPs, worldwide, in adults and children/adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…The anxiety scale measures symptoms that are relatively specific to anxiety disorder [ 6 ]. Scores on the 4DSQ depression and anxiety scales indicate the likelihood of a (DSM-IV) depressive or anxiety disorder [ 7 , 8 ]. The somatization scale measures symptoms of somatic distress and somatoform disorder [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety is a heterogeneous condition exhibiting a wide range of symptom dimensions (Terluin et al, 2014), including panic disorder, generalized anxiety disorder, and specific phobias. Anxiety is a heterogeneous condition exhibiting a wide range of symptom dimensions (Terluin et al, 2014), including panic disorder, generalized anxiety disorder, and specific phobias.…”
Section: Discussionmentioning
confidence: 99%
“…Since our study revealed a significant comorbidity between grapheme-colour synaesthesia and anxiety disorder, we look to possible neural or genetic overlaps between the two conditions. Anxiety is a heterogeneous condition exhibiting a wide range of symptom dimensions (Terluin et al, 2014), including panic disorder, generalized anxiety disorder, and specific phobias. This heterogeneity is reflected in the brain imaging literature on anxiety disorder, with different regions implicated in different underlying behaviours (Duval, Javanbakht, & Liberzon, 2015).…”
Section: Discussionmentioning
confidence: 99%